The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40520-017-0774-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on noninvasive mechanical ventilation in elderly medical intensive care unit patients

Abstract: The frailty is associated with higher NIV application problems, failure and mortality risk in elderly ICU patients. The CFS and EFS frailty scores can be used to predict NIV success and outcomes in ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Most common system involved was hepatobiliary system and liver cirrhosis was most commonly diagnosed disease in that category. Other studies reported sepsis as most common diagnosis in ICU related death, [29,39] which was second common diagnosis in our study. Increased incidence of cirrhosis in our study might be due to the fact that alcoholism was more in patients of our study.…”
Section: Discussionsupporting
confidence: 67%
“…Most common system involved was hepatobiliary system and liver cirrhosis was most commonly diagnosed disease in that category. Other studies reported sepsis as most common diagnosis in ICU related death, [29,39] which was second common diagnosis in our study. Increased incidence of cirrhosis in our study might be due to the fact that alcoholism was more in patients of our study.…”
Section: Discussionsupporting
confidence: 67%
“…Older patients are more likely frail, which is a multifaceted condition characterized by the loss of physiologic and cognitive reserves ( 3 , 4 ). The observational studies suggest that the patients with frailty currently account for up to one-third of the critically ill ( 5 , 6 ). Consequently, the patient outcome is determined not only by the acute critical illness but increasingly by the reduced functional reserve of pre-existing frailty resulting in higher 30-day mortality ( 5 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…
We identified no significant differences in NIV success when age and specific comorbidities were considered [5]. But since patient inclusion criteria of our study were not designed to investigate the answers of these questions we cannot interpret our results as these factors do not have any impact on NIV success.
…”
mentioning
confidence: 71%